Corporate Governance in China. Issue 3 (September 2014) - Morck, Randall; Yeung, Bernard
<x xml:space="preserve">Abstract</x> Since the death of Mao Tse Tung in 1976, China has achieved unprecedented economic growth. Per capita GDP has increased from one of the lowest in the world to a level that is firmly in the middle of the international ranks. But can China continue on the growth path of the last four decades? The question arises because of the tendency of developing economies, having achieved periods of "catch‐up" growth, to become mired in a "middle‐income trap" that appears to stem from a variety of factors, including the tendency for elites and oligarchs to protect their own interests by blocking competition. China's success to date has come without many of the key institutions—notably, private property rights, shareholder‐centered corporate governance, and a well‐functioning impartial legal system—that most Western economists believe essential to long‐term success. China's description of its system as "market socialism with Chinese characteristics" is an accurate one. Markets, not decrees, set most prices, while the state, in the form of the Communist Party, continues to control the careers of SOEs' senior executives, regulators, and government officials, and retains "options" to intervene in a large variety of financial and corporate affairs as well as judicial processes and decisions. Chinese history underpins the system in the sense that the Party is, at least in some respects, a genuine meritocracy reminiscent of the imperial civil service of past eras. And the authors raise the possibility that the Party's Leading Role has actually contributed to China's extraordinary growth not only by fostering such a meritocracy, but by initiating and presiding over what development economists describe as a "Big Push, " a coordinated simultaneous development of many firms in multiple industries that was necessary to transform a subsistence agricultural economy into a modern industrial one. But for all the effectiveness of China's "Big Push, " the authors close by expressing doubt that China can continue to rise into the world's economic upper ranks until it adopts the substance as well as the form of those missing institutions that, they argue, are the only well‐marked path to high‐income status.